Pemberdayaan UMKM Melalui Pelatihan Pengolahan Daging Sapi ASUH di Desa Dungaliyo Kecamatan Dungaliyo Kabupaten Gorontalo - Mukhtar, Muhammad; Sayuti M., Muhammad; Bahri, Syamsul; Antuli, Zainudin (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
This community service program aimed to empower Micro, Small, and Medium Enterprises (MSMEs) in Dungaliyo Village, Dungaliyo Sub-district, Gorontalo Regency through training in beef processing based on the ASUH principles (Safe, Healthy, Whole, and Halal). The training was conducted using a participatory and hands-on approach, involving 30 participants consisting of MSME actors and housewives. The training materials included education on ASUH principles, technical skills for processing value-added beef products such as shredded beef, meatballs, and nuggets, as well as the introduction of simple processing technology and packaging methods. The results of the program showed a significant increase in participants' knowledge and skills regarding hygienic and economically valuable beef processing. The products made during the training met food safety standards and showed potential for further development as independent businesses. Participants' enthusiasm also reflected a growing spirit of local entrepreneurship. This program contributed to strengthening the village's economic capacity and serves as a replicable empowerment model based on local potential